Shopee Coins in the Perspective of Sharia Economic Law - Aang Asari; M. Khoirur Rofiq; Maruf Hidayat; Sukron (Wealth: Journal of Islamic Banking and Finance, 2025)
Shopee is an application that has been available in Indonesia since 2015, providing a variety of features for its users. These include the Shopee Mall, the introduction of ShopeePay, and the launch of Shopee Live, along with rewards in the form of Shopee Coins for loyal customers. These coins can be used as discounts when purchasing products through the Shopee app. However, from the perspective of Islamic legal theory, these features are considered new and require an examination of their validity, including an analysis of the terms and conditions and the identification of the underlying mechanisms. This article focuses on exploring and describing the legal aspects of acquiring and using Shopee Coins. The research conducted for this article is based on library research methods. The author carefully examines and analyzes the information to achieve objective conclusions. The findings indicate that, firstly, the transactions involving Shopee Coin services are permissible and valid, as they meet the necessary terms and conditions. In muamalah jurisprudence, the acquisition of Shopee Coins falls under the Ju'alah contract. Secondly, the expiration period for using Shopee Coins does not impact the validity of obtaining them, since it lacks elements that could invalidate the Ju'alah contract. Nonetheless, Shopee should communicate the expiration provisions for these coins on its application page, ensuring that users are informed and do not feel disadvantaged by the policy.